Health management students’ perceived soft skills acquisition and university commitment - Lior Naamati-Schneider; Dorit Alt (BMC Medical Education)
Abstract University commitment reflects students’ emotional and psychological attachment to their institutions. It is fostered by providing essential resources that empower students to shape their futures. Amidst the increasing demand for universities to bolster students’ soft skills for greater adaptability in the contemporary workforce, this study focuses on examining the connections between skill acquisition and healthcare management students’ commitment levels to their university. Data were gathered by two questionnaires measuring three sets of soft skills acquisition (1) Personal skills (PS) involve a commitment to organizational values, ethical navigation in professional settings, self-awareness, resilience, creativity, self-improvement, and work/life balance; (2) Social skills (SS) encompass clear communication, conflict resolution, networking, multicultural navigation, leadership, and fostering collaborative relationships; and (3) Methodological skills (MS) include adaptability, insightful synthesis of information, continuous improvement, customer satisfaction, proactive decision-making, goal setting, resource management, and results-oriented organizational leadership. The results indicated that students have acquired more methodological soft skills compared to personal or social ones. Structural equation modeling (SEM) results showed that among the categories of soft skills, personal, social, methodological, merely the latter was significantly related to university commitment. Methodological skills, including adaptability, analysis, and decision-making, were directly related to university commitment, aligning with educational and professional goals, offering a stronger connection to academic success than personal or social skills. This study emphasizes the need for higher education institutions to improve their curriculum to better develop soft skills. Prioritizing personal and social abilities alongside technical skills is crucial to preparing students for future career challenges, particularly in healthcare.